2018
DOI: 10.1055/a-0801-8730
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fat Oxidation During Exercise in Post-Menopausal Overweight-Obese Women with Higher Lipid Accumulation Product Index

Abstract: Background and Aims The main aim of this study was to analyze how the lipid accumulation affects the whole-body fat oxidation over a range of intensities during a submaximal incremental exercise test in post-menopausal overweight-obese women. Patients and Methods The maximal fat oxidation (MFO), the intensity where the MFO occurs (FatMax), fat oxidation were measured over a range of intensities during a submaximal incremental exercise test through indirect calorimetry in 60 postmenopausal overweight-obese wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our results further indicated that cardiovascular risk parameters were related to the occurrence of an abnormal LAP index, for which the cutoff point was 34.2 cm × mmol/L, above which, the risk of metabolic syndrome is increased [28]. In line with previous literature [29], our results indicate a significantly greater LAP index in the OW group compared to that in the NW group both before and after the intervention, indicating an unhealthy metabolic phenotype for women with obesity. However, women with obesity showed a decrease in LAP in response to IC training (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…Our results further indicated that cardiovascular risk parameters were related to the occurrence of an abnormal LAP index, for which the cutoff point was 34.2 cm × mmol/L, above which, the risk of metabolic syndrome is increased [28]. In line with previous literature [29], our results indicate a significantly greater LAP index in the OW group compared to that in the NW group both before and after the intervention, indicating an unhealthy metabolic phenotype for women with obesity. However, women with obesity showed a decrease in LAP in response to IC training (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…The American Heart Association and the American College of Sports Medicine both advise older women to engage in exercise because it is a low-cost intervention that has numerous advantages for women's health after menopause [57]. In their study of postmenopausal overweight/obese women's whole-body fat oxidation during acute treadmill activity, Stein and colleagues [58] discovered an antagonistic association between metabolic health and the capacity to burn fat in response to aerobic exercise. This shows that higher metabolic rigidity is linked to increased lipid accumulation, which results in increased body fat and visceral fat distribution [59].…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, previous studies had shown that hederagenin could effectively treat tumors through anti-oxidation (Kim et al 2017a) and antiinflammation (Lee et al 2015). Lowering blood lipids is often closely related to properties of antioxidation (Stein et al 2020 (Canesi et al 2019). However, there are no studies have reported that hederagenin can decrease blood lipid.…”
Section: Discussionmentioning
confidence: 99%